2001
DOI: 10.1053/joca.2001.0412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chondrocyte cell-associated matrix metabolism by flow cytometry

Abstract: Flow cytometry offers an efficient tool to study the metabolism of the chondrocyte CAM. The MFI has been used as a parameter to quantify the ECM molecules in the CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…Monolayer cultures were trypsinized, resuspended in complete media, then mixed 1:1 with 0.8% low melt agarose (Life Technologies, Rockville, MD) in DMEM at 37°C (before gelling), giving a final concentration of 1 × 10 4 cells/ml suspended in 0.4% low melt agarose. Eight milliliter were pipeted into 10‐cm tissue culture plates that were previously coated with 8 ml of 0.7% low melt agarose in DMEM, 10% FBS (Robson et al, 2000; Wang et al, 2001) which yielded a total of 16 ml of agarose‐media to 8 × 10 4 cells. The agarose was allowed to gel at room temperature, and then placed in a 37°C, 5% CO 2 humidified incubator for 3–4 weeks to allow cell cluster growth to reach quantifiable size and number.…”
Section: Methodsmentioning
confidence: 99%
“…Monolayer cultures were trypsinized, resuspended in complete media, then mixed 1:1 with 0.8% low melt agarose (Life Technologies, Rockville, MD) in DMEM at 37°C (before gelling), giving a final concentration of 1 × 10 4 cells/ml suspended in 0.4% low melt agarose. Eight milliliter were pipeted into 10‐cm tissue culture plates that were previously coated with 8 ml of 0.7% low melt agarose in DMEM, 10% FBS (Robson et al, 2000; Wang et al, 2001) which yielded a total of 16 ml of agarose‐media to 8 × 10 4 cells. The agarose was allowed to gel at room temperature, and then placed in a 37°C, 5% CO 2 humidified incubator for 3–4 weeks to allow cell cluster growth to reach quantifiable size and number.…”
Section: Methodsmentioning
confidence: 99%
“…Cartilage ECM is formed and maintained by chondrocytes (12)(13)(14)(15). Although the mechanisms of ECM turnover and homeostasis have not been studied in great detail, research in several laboratories has substantiated the importance of cartilage-specific collagens and the large aggregating proteoglycan aggrecan in the maintenance of cartilage integrity and homeostasis (12)(13)(14)(15). Extensive research has also confirmed the importance of the sex-determining region Y-type high mobility group box (SOX) family of high mobility group transcription factors (L-SOX5, SOX6, and SOX9) in the expression of cartilage-specific proteins (13).…”
mentioning
confidence: 99%
“…The MFI of the cell samples was then analyzed without changing any of the instrument settings. The reproducibility and reliability of this procedure have been demonstrated previously (36, 38).…”
Section: Methodsmentioning
confidence: 58%
“…Cells were gated on forward and side scatter to exclude dead cells, debris, and aggregates. Propidium iodide was additionally used to exclude dead cells when the epitopes outside the cells (i.e., IGFRI, IL‐1RI, and IL‐1RII) and the ECM molecules were analyzed (36, 38). The mean fluorescence intensity (MFI) of the positive cell population, which is due to the binding of the conjugated antibodies to the specific antigen, was used to quantify the presence of IGFRI, IL‐1RI, and IL‐1RII on the plasma membrane, the ECM molecules in the CAM, and the accumulation of IGF‐1, IL‐1α, and IL‐1β inside the cells.…”
Section: Methodsmentioning
confidence: 99%